PENGARUHI KUALITAS PELAYANAN JASA GOJEK TERHADAP KEPUASAN PELANGGAN DI KOTA MEDAN - Silaban, Frederick Saroha; Silaban, Pasaman (Jurnal Manajemen dan Bisnis, 2024)
This research aims to investigate the influence of service quality consisting of responsiveness, guarantee, physical evidence, empathy and reliability on customer satisfaction. This research collected data using a questionnaire method and conducted a survey of 210 consumers who had experience using Gojek services in Medan City. Data analysis was carried out using a multiple regression approach using SPSS Version 25 software. The results show that of the five dimensions of service quality, only two aspects, namely responsiveness and reliability, can increase satisfaction. Meanwhile, the other three dimensions of service quality, namely guarantee, physical evidence and empathy, cannot increase consumer satisfaction.